Reducing the energy consumption of a hospital during the development process – An applied study on Hama National Hospital in Hama – Syria –: خفض استهلاك الطاقة لمستشفى خلال عملية التطوير – دراسة تطبيقية على مستشفى حماة الوطني بمدينة حماة - سورية – - Ola Omar Harba, Louai Haider Merhej (مجلة العلوم الهندسية و تكنولوجيا المعلومات, 2021)
The health system in Syria is based on the principle of free access and free care in public hospitals called national hospitals. However, most of these hospitals were built in the twentieth century and need a development process to reduce their consumption, which is of financial benefit in reducing operating costs to be used in health care support. To benefit the environment, and given that modern technology, especially nanotechnology, has provided materials with high efficiency, but it has not been taken into account so far in Syria, the research is working on developing a mechanism for developing hospitals based on nanotechnology and applying it to the Hama National Hospital located in the city of Hama to be a reference to develop the rest of the Syrian hospitals.